Clinical manifestation and laboratory data of illicit drugs versus other substances intoxication in children - Leila Barati; Mohammadali Vakili; Omid Mehrpour; Mehrdad Teimoorian (Scientific Reports)
Abstract Children are highly sensitive to toxins which can damage their organs and lead to death. Investigating the main causes of intoxication could reduce mortality and morbidity in children. In this cross-sectional study, the documents of all poisoned patients (214 cases) admitted to the emergency department of Taleghani children`s Hospital between April 2020 and 2023 were investigated. Approximately 51% of them were females. There were 87 cases (45.3%) of illicit drug poisoning, which included methadone 43.8%, opium 41.4%, amphetamine 8.2%, cannabis 3.3%, buprenorphine 2.2%, and tramadol 1.1%. Children who were poisoned by illicit drugs presented with impaired level of consciousness (92.5%), unstable vital signs and abnormal laboratory results. The level of serum glucose was higher in methadone toxicity. Three and two cases, due to methadone and opium poisoning died. Children with illicit drugs poisoning in terms of vital signs and laboratory data were worse compared to other poisonings and mortality is high in this group. In this study, the blood sugar in methadone poisoning cases was statistically significantly different from other drugs, and it is suggested that in cases of children suspected of poisoning with illicit drugs and high blood sugar, methadone poisoning should be considered in the differential diagnosis.